NanoKnife a dva úspěšné případy intrakavitální ireverzibilní elektroporatizace nádorů hlavního bronchu - Fanta, J; Horák, P; Marvan, J; Mašek, M; Kašpar, M; Pauk, N; Dvořák, J (Rozhledy v chirurgii, 2012)
We have used the method of irreversible electroporation (IRE) twice to treat central non-small cell lung tumours. Both tumours obstructed the right main stem bronchus. Due to a high risk of right-sided pneumonectomy we chose to apply the tissue sparing device called NanoKnife and an alternative IRE method. The first surgery was performed in August 2011 and the second one in June 2012. The first case was an epidermoid carcinoma, 3 cm in size, which completely obstructed the right main stem bronchus on the boundary line with the upper lobar bronchus and caused lung atelectasis. The second case was a carcinoid, 2 cm in size, which grew from the main stem bronchus to the carina. Pneumonectomy was contraindicated due to lung function in the first case, and the other patient preferred the IRE method to radical but risky resection with bronchoplasty. IRE was performed through open thoracotomy. No complications were detected after the surgery in both cases. The first patient was discharged on the 12th postoperative day and the second one on the 5th postoperative day. 98% regression of the tumour was detected by CT scan in the first patient, and complete regression occurred in the case of the second one. 100% apoptosis and "disparition" of the carcinoma in the first case was verified by bronchoscopy and cytology after 6 months. Both patients remain in follow-up after surgery using the IRE method and are without subjective or objective complaints and without any signs of tumour recurrence. NanoKnife and IRE without lung resection resulted in the destruction of lung tumours while preserving the lung parenchyma and pulmonary functions.
Keywords: nádory plic; Aged; spinocelulární karcinom; Carcinoma, Squamous Cell; Lung Neoplasms; Humans; Electrochemotherapy; Carcinoma, Bronchogenic; senioři; lidé; Middle Aged; lidé středního věku; elektrochemoterapie; bronchogenní karcinom